The Capability Approach: Comparing Amartya Sen and Martha Nussbaum - Saigaran, Nithiya Guna; Karupiah, Premalatha; Gopal, Parthiban S. (2015)
Capability approach pioneered by Amartya Sen has been a new milestone for analyzing poverty through gender perspective. Since the introduction of the approach, numerous scholars from various fields have applied this approach in their studies. One of the prominent scholars who has contributed and expanded the approach is Martha Nussbaum. Though there have been some agreements but the arguments between the two scholars have shed new insights about the poor and their situation. Therefore, this paper attempts to compare Sen‘s and Nussbaum‘s capability approach by focusing on their core concepts, main arguments and rationality of the criticism of the approach. The methodology of this paper is based on document research.